Bibliographic Data - Jankauskas, Rimantas (Acta medica Lituanica, 2020)
Lithuania language editor Danutė Petrauskienė English language editor VTeX Cover design Jurga Tėvelienė Layout Vida Vaidakavičienė Authors are responsible for the content of their work Vilnius University Press 9 Saulėtekio Av., III Building, LT-10222 Vilnius info@leidykla.vu.lt, www.leidykla.vu.lt/en/ Books Online knygynas.vu.lt Vilnius University Press Scholarly Journals zurnalai.vu.lt Printed by UAB „Ciklonas“ 68 Žirmūnų St., LT-09124 Vilnius Print run 50 copies. 4.7 author’s sheet